The Takotsubo Syndrome (Syndrome of the broken heart): Hormonal aspects (Research, Society and Development, 2021)
Takotsubo's syndrome is seen as a reversible acute heart failure that results from catecholaminergic myocardial stunning, with chest pain and dyspnoea as its main symptoms. The study aimed to search the literature for evidence about the hormonal influence on the onset of takotsubo syndrome. An integrative literature review was carried out by searching the Virtual Health Library (VHL), using the descriptors Cardiomyopathy of takotsubo, Catecholamines, Diagnosis, including complete articles, available in Portuguese, English or Spanish, published between 2010 and 2020. After careful analysis of the results obtained, 10 studies were selected to compose the research. The results showed a strong relationship between hormonal release and the onset of the syndrome. Catecholamines released from hypostimulation of the hipothalamus-pituitary-adrenal system have important effects on the speed of contractility and the force of contraction of the heart muscle, resulting in disruption of cardiac function and the appearance of the syndrome. It is also concluded that the increased release of these hormones is mainly stimulated by stressful situations, such as emotional trauma and surgical stress. The need for further studies in the area, such as clinical trials, to provide more evidence of this hormonal activity in the onset of takotsubo syndrome, as well as the performance of national studies, considering that the vast majority of studies are international.